VD_FINDINFO Jug / 2011 / 274 vom 24. Juni 2011 - VD Tribunal cantonal (2011)
LÉSION CORPORELLE SIMPLE | 106 CP, 123 ch. 1 CP, 123 ch. 2 CP, 34 CP, 42 CP, 44 CP, 47 CP, 50 CP, 398 al. 3 let. a CPP (CH), 398 al. 3 let. b CPP (CH)